Wochenmärkte, Marktorte und Marktzyklen in Vorderasien - Gaube, H.; Grötzbach, E.; Niewöhner-Eberhard, E.; Oettinger, B.; Wirth, E. (ERDKUNDE, 1976)
The introductory survey Concerning the theory of periodic markets from the viewpoint of economics and geography begins by pointing out those economic forces and patterns which form the basis of all periodic markets and market systems in the world. It is evident that even traditional systems of periodic markets are very flexible in the face of modern developments. Periodic markets can therefore be found almost everywhere in the Third World, where, in connection with economic and technical opening up, the traditional subsistence economy gives way to production for a larger home market or the world market. Against the background of such worldwide patterns such differences in various cultural areas of the world have for some years also come to be investigated to an increasing extent as they arise from each specific social and cultural situation; they have succeeded in coining systems of periodic markets in ways that vary from region to region. Whereas tropical West Africa, as well as East Africa and Latin America, have been well researched in numerous publications, there are to date too few investigations of periodic marketing in the countries of the Middle East culture area. To provide a rough outline four examples will be employed to demonstrate the wide range of phe nomena encountered in the periodic markets of the Near East. The first contribution on Periodic markets in Afghanistan, shows that following an increase in population density and economic development, there are now considerably more periodic markets in Afghanistan than there were in the 19th century. In smaller towns, periodic markets affect the static urban bazaars as well, for here most shops are only open on markets days. In large parts of northern Afghanistan markets are held on Monday and Thursday only. It has thus not proved possible to form market circuits, whereby neighbouring markets are intentionally held on different days in order to enable them to be visited by travelling salesmen. The investigation concerned with The weekly markets and their rotations in west central Anatolia demonstrates, on the other hand, that in large areas of Turkey market rings and market systems are already developed in an almost classic manner. Clearly demonstrated spatial rotations in the forwarding of goods to weekly markets by travelling salesmen can be identified; as a rule neighbouring villages hold their market on successive days. Medium sized and larger towns also hold weekly markets in addition to their daily stationary market. The goods on offer in these markets do not, however, compete with those of the shops, but rather complement them. The report on Daily Suq and weekly market in Sa’ada, Yemen, illustrates a totally different aspect of periodic marketing; in southern Arabia the periodic market is a matter of tribal authority, which is in consequence held on the edge of the village or even away from all settlements, as opposed to the bazaar with its permanent buildings in the centre of town, which is an institution of the central state authority. A highly interesting mixed form occurs in Sa’ada, a small Yemeni town, the historic roots of which are explained. The urban bazaar now appears largely to be included in the periodic marketing of the northern Yemen; only on market days does it enjoy a greater range of goods exhibited and of visitors. Finally, there is a short analysis of The weekly market in Hanasir, northern Syria, Hansasir is a small town situated in a recently settled region of Syria. A weekly market was established there in 1950, with the definite economic purpose of improving the provisions for the urban population and the settlers in the surrounding hinterland. After some modest success during the first years, this rather peripherally located market now suffers from the consequences of the land reform, which has been pushed through since 1963, and the expropriations and state take-overs connected with it. In others parts of Syria these influences, of state or co operative marketing systems, have brought about the disappearance of most weekly markets.